Artificial Intelligence & Its Contemporary Applications in Dentistry (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Artificial intelligence (AI) has been used in a variety of ways in healthcare. It is a field of both engineering and science,associated with the perceptive of intelligent behavior, and creating artifacts that replicate such behavior. Technology has been the biggest innovation in every industry, Dental care is no different. Artificial Intelligence can serve as a useful modality in diagnosis and treatment of lesions of the oral cavity and can be employed in screening and classifying suspicious altered oral mucosa undergoing premalignant and malignant changes. This field can be explored tremendously for easy diagnosis, proper treatment and satisfying outcome.